ANALISIS KESALAHAN SISWA SMA NEGERI DI KOTA CIMAHI DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI TRIGONOMETRI - Ardy Fauzi Rachman; Ratni Purwasih (IKIP Siliwangi, 2021)
This research aims to examine the mistakes of Grade X high school students in the City of Cimahi and the factors that cause errors in solving trigonometric problems. This research was conducted at Cimahi 2 Public High School, 3 Cimahi Public High School, Cimahi 4 Public High School which each sample was taken in 1 class. The number of subjects in this study were 65 students. The research approach used is qualitative descriptive method. Data collection techniques used were test and interview instruments. The test instrument used in this study is a matter of the National Examination on trigonometry material as many as 5 questions that have been validated. Interview technique is used to find out the factors that cause students' mistakes. Error criteria used by researchers according to Hadar. The results showed the percentage based on the criteria for error as follows: (1) Error using data by 5.48%, (2) Error using language by 24.66%, (3) Error using logic to draw conclusions of 0%, (4) Error using definition or theorem of 12.33%, (5) Completion was not re-examined by 22.6%, and (6) Technical error of 34.93%. Factors that cause students' mistakes such as inaccurate students when turning problems into mathematical models, students forget to use the right formula in solving problems, errors in the calculation process, students do not like math lessons, and the problem is difficult to understand.